2012
DOI: 10.1002/jmor.20034
|View full text |Cite
|
Sign up to set email alerts
|

Development of the follicle complex and oocyte staging in red drum, sciaenops ocellatus linnaeus, 1776 (perciformes, sciaenidae)

Abstract: Pelagic egg development in red drum, Sciaenops ocellatus, is described using tiered staging. Based on mitosis and meiosis, there are five periods: Mitosis of Oogonia, Active Meiosis I, Arrested Meiosis I, Active Meiosis II, and Arrested Meiosis II. The Periods are divided into six stages: Mitotic Division of Oogonia, Chromatin Nucleolus, Primary Growth, Secondary Growth, Oocyte Maturation and Ovulation. The Chromatin Nucleolus Stage is divided into four steps: Leptotene, Zygotene, Pachytene, and Early Diploten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
94
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(106 citation statements)
references
References 64 publications
(161 reference statements)
9
94
0
3
Order By: Relevance
“…In anurans, cystoblasts were located within germ cell nests and in germ patches on the surface of the ovaries (Kloc et al , ; Ogielska & Kotusz, ). Investigations of sexually mature teleosts have shown that within their ovaries germline stem cells, cystoblasts and cysts composed of cystocytes were located peripherally in germ cell nests, also termed oogonia nests (Grier et al , ; Quagio‐Grassiotto et al , ; Grier, ; Wildner et al , ). In the ovary of the spotted pimelodus Pimelodus maculatus Lacépède 1803, undifferentiated cells (germline stem cells) and differentiated cells (cystoblasts) were distinguished.…”
Section: Introductionmentioning
confidence: 99%
“…In anurans, cystoblasts were located within germ cell nests and in germ patches on the surface of the ovaries (Kloc et al , ; Ogielska & Kotusz, ). Investigations of sexually mature teleosts have shown that within their ovaries germline stem cells, cystoblasts and cysts composed of cystocytes were located peripherally in germ cell nests, also termed oogonia nests (Grier et al , ; Quagio‐Grassiotto et al , ; Grier, ; Wildner et al , ). In the ovary of the spotted pimelodus Pimelodus maculatus Lacépède 1803, undifferentiated cells (germline stem cells) and differentiated cells (cystoblasts) were distinguished.…”
Section: Introductionmentioning
confidence: 99%
“…This need for further analysis is particularly the case for the extra-testicular ducts and OE to distinguish the regenerating and regression phases as described by Brown-Peterson et al (2011), if these phases are present in this species. On the other hand, the proposal of Brown-Peterson et al (2011) is not adaptable to all teleosts because interspecific variations in fish oocyte development do not lend themselves to a standard terminology across all fishes (Grier 2012). Specific for elasmobranchs, the proposal of ICES (2013) includes a unique scale for viviparous species, despite the large number of reproductive strategies available within this group, until scientific evidence suggests otherwise (ICES 2013).…”
Section: Adequacy Of Recent General Maturity Scalesmentioning
confidence: 99%
“…Yet, specific characteristics from gonad development do not correlate directly with the reproductive cycles or modes (Koob & Callard 1999), and consequently general scales based on appearances of the reproductive tract will likely benefit from considering the gonad development type apart from the reproductive mode. Notwithstanding, staging schemes need to be adaptable to species' variations that can account for the extreme reproductive diversity of fishes (Grier 2012), which indicates the need for the development of adaptable staging techniques. Additionally, Poulakis (2013) pointed out the importance of considering the methods used to as sign maturity and the consistency of these across studies.…”
Section: Adequacy Of Recent General Maturity Scalesmentioning
confidence: 99%
See 2 more Smart Citations